1985
DOI: 10.3382/ps.0640370
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Protein Turnover in the Skeletal Muscles of Broiler Chicks

Abstract: Growth and protein turnover were examined in the breast (pectoralis thoracica) and the leg (gastrocnemius-peroneus) muscles of broiler chicks at 1, 2, 4, and 6 weeks posthatching. The fractional rate of protein synthesis (ks) was measured by an isotope emulsion method. The fractional degradation rate (kd) was calculated from the difference in ks and fractional deposition rate (kg), which was estimated from regression equations of muscle size and protein content on body weights. The growth rate (%/day) of skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
5

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 25 publications
(27 reference statements)
3
23
1
5
Order By: Relevance
“…Previous studies have shown that the fractional rate of protein synthesis decreases with age in skeletal muscle in both mammals (Davis et al, 1989(Davis et al, , 2009) and chickens (Kang et al, 1985;Maeda et al, 1984;Tesseraud et al, 1996). For example, Kang et al (1985) reported that the fractional synthesis rate in the breast muscle decreased by more than 50% between 1-and 2-week old chickens, and then continued to slowly decrease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the fractional rate of protein synthesis decreases with age in skeletal muscle in both mammals (Davis et al, 1989(Davis et al, , 2009) and chickens (Kang et al, 1985;Maeda et al, 1984;Tesseraud et al, 1996). For example, Kang et al (1985) reported that the fractional synthesis rate in the breast muscle decreased by more than 50% between 1-and 2-week old chickens, and then continued to slowly decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the important selection traits change according to production and market trends, growth rate has consistently been the prime selection trait because of its large impact on total meat production cost (Arthur and Albers, 2003). However, growth rate was reported to decrease with age in chickens (Kang et al, 1985;Reiprich et al, 1995), suggesting that the regulation of protein turnover changes with age in chicken skeletal muscle. For example, fractional rates of protein synthesis have been shown to decrease in chicken breast muscle during the period of 1-4 weeks of age, but the fractional protein degradation rate changed little to none during the same period (Kang et al, 1985;Tesseraud et al, 1996).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Desta forma, o peso relativo do músculo esquelé-tico, mais precisamente o peitoral, dobra nos cinco primeiros dias após a eclosão . O ganho de peso do músculo peitoral e das pernas com uma semana de idade, representa 6% e 2% do peso vivo da ave, respectivamente KANG;SUNDE;SWICK, 1985).…”
Section: Lista De Figurasunclassified
“…Desta forma, o peso relativo do músculo esquelé-tico, mais precisamente o peitoral, dobra nos cinco primeiros dias após a eclosão . O ganho de peso do músculo peitoral e das pernas com uma semana de idade, representa 6% e 2% do peso vivo da ave, respectivamente KANG;SUNDE;SWICK, 1985).A formação da fibra muscular esquelética é finalizada ao nascimento/eclosão nos mamí-feros/aves sendo que depois deste momento, em condições normais, não é possível a realização de mitose das miofibrilas. Entretanto, um grande aumento no conteúdo de DNA muscular, é observado durante o crescimento pós-eclosão das aves, sendo este processo essencial para a hipertrofia muscular.…”
unclassified